Characterization of Thermal Protective Clothing under Hot Water and Pressurized Steam Exposure. Issue 5 (September 2014) - Mandal, Sumit; Lu, Yehu; Wang, Faming; Song, Guowen
In this study, fabric materials used in thermal protective clothing (TPC) were characterized under hot water and pressurized steam exposures. Some selected TPC were tested using a newly developed full-scale hot-water spray manikin test. Thermal energy transmission through fabric materials and clothing was investigated. A layered fabric system comprised of a moisture barrier in the outer layer immediately stopped mass transfer and showed high performance. Fabric properties such as air permeability, thickness, clothing size, and size of the air gap between wearers' bodies and clothing did affect the performance by controlling heat and mass transfer through fabrics. An air-impermeable thick fabric system demonstrated higher performance than an air-permeable thin fabric system. The relationship between fabric materials' properties, clothing features, and clothing protective performance was summarized.